Gastrointestinal jumbo phages possess independent synthesis and utilization systems of NAD+ - Cunyuan Li; Kaiping Liu; Chengxiang Gu; Ming Li; Ping Zhou; Linxing Chen; Shize Sun; Xiaoyue Li; Limin Wang; Wei Ni; Meng Li; Shengwei Hu (Microbiome)
Abstract Background Jumbo phages, phages with genomes > 200 kbp, contain some unique genes for successful reproduction in their bacterial hosts. Due to complex and massive genomes analogous to those of small-celled bacteria, how jumbo phages complete their life cycle remains largely undefined. Results In this study, we assembled 668 high-quality jumbo phage genomes from over 15 terabytes (TB) of intestinal metagenomic data from 955 samples of 5 animal species (cow, sheep, pig, horse, and deer). Within them, we obtained a complete genome of 716 kbp in length, which is the largest phage genome so far reported in the gut environments. Interestingly, 174 out of the 668 jumbo phages were found to encode all genes required for the synthesis of NAD+ by the salvage pathway or Preiss-Handler pathway, referred to as NAD-jumbo phage. Besides synthesis genes of NAD+, these NAD-jumbo phages also encode at least 15 types of NAD+-consuming enzyme genes involved in DNA replication, DNA repair, and counterdefense, suggesting that these phages not only have the capacity to synthesize NAD+ but also redirect NAD+ metabolism towards phage propagation need in hosts. Phylogenetic analysis and environmental survey indicated NAD-jumbo phages are widely present in the Earth’s ecosystems, including the human gut, lakes, salt ponds, mine tailings, and seawater. Conclusion In summary, this study expands our understanding of the diversity and survival strategies of phages, and an in-depth study of the NAD-jumbo phages is crucial for understanding their role in ecological regulation. Video Abstract